Side-Information Generation for Temporally and Spatially Scalable Wyner-Ziv Codecs. (25th March 2009) - Macchiavello, Bruno; Brandi, Fernanda; Peixoto, Eduardo; de Queiroz, Ricardo L.; Mukherjee, Debargha
Abstract : The distributed video coding paradigm enables video codecs to operate with reversed complexity, in which the complexity is shifted from the encoder toward the decoder. Its performance is heavily dependent on the quality of the side information generated by motio estimation at the decoder. We compare the rate-distortion performance of different side-information estimators, for both temporally and spatially scalable Wyner-Ziv codecs. For the temporally scalable codec we compared an established method with a new algorithm that uses a linear-motion model to produce side-information. As a continuation of previous works, in this paper, we propose to use a super-resolution method to upsample the nonkey frame, for the spatial scalable codec, using the key frames as reference. We verify the performance of the spatial scalable WZ coding using the state-of-the-art video coding standard H.264/AVC.